Tourism Development in South Asia Region: Challenges and Opportunities - PATIL, SNEHAL; JAYBHAYE, RAVINDRA (Turizam, 2023)
Tourism development in the South Asian region has gained significant attention in recent years due to its potential to contribute in economic growth, poverty reduction and regional integration. However, this region faces several challenges including political instability, security concerns, insufficient infrastructure, and limited coordination among stakeholders. This paper aims to provide a comprehensive overview of the challenges and opportunities for tourism development in the South Asian region. This paper uses the SWOT model and a derived matrix for sustainable growth in the South Asian tourism industry. The data sources for the study are related literature reviews, field observations, interviews with professionals and questionnaires distributed to 100 international travellers. To analyse strategic factors of the country's tourism industry internal strengths and weaknesses as well as external opportunities and threats were identified, followed by strategic planning based on the SWOT matrix and weighted decision matrix. The findings concern both the use of the SWOT technique as a research method and an assessment of the tourism potential of South Asia. The findings of the analysis reveal that, tourism development strategies have to implement includes promoting travel as a driver of economic expansion and job creation, establishing public-private partnerships and integrated marketing campaigns, collaborating on human resource development, improving the quality of facilities and infrastructure, promoting attractions on an on-going basis on a national and international level and developing various  tourist attraction products with the participation of independent, small-scale tourism service providers. Overall, this study can provide valuable insights into the region's potential for growth and collaboration, helping to promote economic development and cultural exchange across the region.Keywords: SWOT analysis, tourism, tourism development strategy, weighted decision matrix